Caracterización de un jabón en barra elaborado con saponinas del Agave (Furcraea andina) y Jaboncillo (Sapindus saponaria L.) incorporando el aceite de las semillas de Cannabis (Cannabis sativa L. - Loachamín Moposa, Wendy Vanessa (2022)
The purpose of this research study was to characterize a bar soap made with saponins from Agave (Furcraea andina) and Jaboncillo (Sapindus saponaria L.) incorporating Cannabis (Cannabis sativa L.) seed oil", taking advantage of organic compounds as alternatives to synthetic additives in cosmetic manufacturing processes. The saponins were extracted by the soxhlet method, using solvents such as methanol (agave saponins), ethanol and distilled water (soap saponins), different treatments were elaborated with two concentrations: 20 and 25 mL oil plus agave saponins at 75 and 80 mL and 20 and 25 mL oil plus soap saponins at 75 and 80 mL, determining the physicochemical parameters (pH, humidity) and surfactant properties (amount of foam) of the soap. ADEVA was performed to identify the best treatments (t7 and t8) and physicochemical analysis according to NTE INEN 841. t7 has a pH value of 9.36, moisture and volatile matter 30.60 %, total fat 34.74 % and anionic surfactants 6.80 % and t8 a pH value of 9.59, moisture and volatile matter 36.40 %, total fat 29.84 % and anionic surfactants 13.26 %, being within the established parameters. A study was carried out to estimate the production cost and sales price, which yielded values of $ 1.40 and $ 1.42, respectively.